Agents of Grace - Ali Altaf Mian (American Journal of Islam and Society, 2022)
This article contributes to theorizations of ethical agency in the anthropology of Islam by turning to the medieval moral theologian Abū āmid al-Ghazālī (1058-1111). Building on Talal Asad’s engagement with Ghazālī, this article closely reads the latter’s writing on intentionality, which amply illuminates his theory of ethical agency. Ghazālī neither elaborates an idealist theory of ethical agency nor  posits an ethical subject whose practices are “directed at making certain kinds of behaviors unconscious or nondeliberative” (Saba  Mahmood, Politics of Piety, 139). Rather, he articulates ethical agency as a site of contingency and ambivalence, as action involves not  only knowledge, resolution/will, and bodily capacity but also divine grace. Grace, this article argues, is a cipher for the non-sovereignty  of the ethical subject, since for Ghazālī agency is split between the subject’s discursive and material capacities (knowledge, resolution, and bodily strength) and a certain metamorphic spontaneity/enablement that is experienced as a gift of the Other (grace). By turning  to Ghazālī, then, this article encourages serious engagement with the concept of grace for understanding ethical agency in the anthropology of Islam.